Environmental triggers of pemphigus vulgaris and bullous pemphigoid: a case control study - Stone, Corey; Bak, Grace; Oh, Daniel; Zhao, Cathy; Venugopal, Supriya; Kumar, Kuldeep; Murrell, Dedee F. (Frontiers in Medicine, 2024)
Background Previous case–control studies have suggested that environmental factors including exposure to pesticides and organic materials, diet and medications have an important role in the pathogenesis of pemphigus vulgaris. These studies lacked geographical population controls and had less than three controls per case. Objective To identify environmental and occupational risk factors associated with the development of pemphigus vulgaris (PV) and bullous pemphigoid (BP). Method Cases were patients with PV (n = 25) and BP (n = 29) recruited from 2009 to 2017. Controls for PV (n = 72) and BP (n = 84) were recruited from the general population via electoral commission matching, matched for age, sex, residential location, and ethnicity. Data about demographics, environmental exposures and occupational exposures, was collected using a structured questionnaire. Conditional logistic regression analysis was undertaken using SPSS software to identify significant variables. Results Significant factors associated with PV included the daily consumption of leeks (odds ratio (OR) 3.6; p = 0.025), mustard oil (OR = 4.4; p = 0.049), tomatoes (OR = 4.735; p = 0.032), multivitamins (OR 3.6; p = 0.009), alcohol (0.039), and calcium supplements (OR = 44, p < 0.001). Other associated factors included the number of lifetime sunburns (p = 0.019), high levels of mental stress (p < 0.001), and the use of lime household cleaning products (p < 0.001), Significant factors associated with BP included the daily consumption of green or herbal tea (OR = 3.7; p = 0.004), fish oil (OR = 5.7; p < 0.001), calcium supplements (OR = 6.1; p < 0.001), multivitamins (OR = 2.6; p = 0.043), and glucosamine (OR = 3.0; p = 0.046). The use of lime household cleaning products (p < 0.001) and high levels of mental stress (p = 0.007) were also associated with BP. Conclusion Dietary factors containing thiol groups such as leeks, tomatoes, and mustard oil may be potential triggers for PV. High levels of mental stress, the use of supplementary medications such as calcium and multivitamins, and chemical cleaning products containing lime may be associated with an increased risk of developing both PV and BP. Lifestyle changes should be part of routine management for these patients.